Scientific trends on research on denture stomatitis based on Scopus database: A bibliometric analysis - Alam, B.; Nayab, T.; Bugshan, AS; Gad, MM; Khan, E.; Ali, S. (Journal of clinical and experimental dentistry, 2023)
Denture stomatitis is a clinical condition that affects people who wear removable maxillary dentures. It causes redness, soreness, and erythema and ultimately affects the general condition of the patient. The objective of this study was to analyze the leading countries, journals, organizations, and authors and the frequently used keywords associated with denture stomatitis. A bibliometric analysis of publications indexed in the Scopus database was conducted, and the article titles, abstracts, and keywords were analyzed using the VOSviewer software. Denture stomatitis-related publications from 1960 to 2021 were collected. This study included only research papers published in English with "article" as the paper type and dentistry as the subject area. Data from a total of 461 articles and 10 different journals were obtained. The papers were published in 64 different countries. Brazil and the United States of America were the top contributing countries, and the University of Sydney was the leading organization. Papers published in the Journal of Oral Rehabilitation received the highest number of citations, while author Gordon Ramage from the University of Glasgow received the highest number of citations. The bibliometric analysis revealed that the number of denture stomatitis-related publications indexed in the Scopus database is increasing globally. Since 2007, there has been an increase in research interest regarding denture stomatitis, with more publications from several countries expected to be published in different journals. Bibliometric analysis, denture, candida, VOSviewer, maxilla.